Verder: Beckett en de 21e eeuw - Kosters, Onno; Engelberts, Matthijs (Amsterdam University Press, 2008)
Literature (Belles lettres) and rhetoric; Culture and institutions; Dutch literature; Dutch and Flemish literature; Stage presentations